Triad of minimal antenatal care, pre-eclampsia and dementia in rural women: a deep insight and call for awareness - Wardah Navaid; Syeda Tayyaba Rehan; Mahnoor Rehan Hashmi (Journal of the Pakistan Medical Association, 2022)
Pre-eclampsia, a prominent gestational hypertensive disorder, affects around 2-8% of pregnancies and is the dominating cause of late- life maternal morbidities worldwide. Frequent signs of this disorder such as proteinuria, hypertension, and thrombocytopenia, are detected by physicians during the routine antenatal checkups of expectant women. Pre-eclampsia, if left untreated, delineates with complications like central nervous system dysfunction, microangiopathies, thromboembolism, and cerebrovascular accidents in later life of women.[1] Vascular dementia is noticed as one of the late-life complications in women with a history of preeclampsia. Two cohort analyses disclosed a significantly increased risk of vascular dementia in later life of women with a history of preeclampsia. [2,3] Incidence of vascular dementia was noticed as being thrice more common in these women when compared to the non-pre-eclamptic ones. [2] Like all over the world, high percentage of pre-eclampsia cases are also rampant in the rural areas of Pakistan. An analysis from Sukkar, rural Sindh, Pakistan, showed that Preeclampsia and eclampsia cases in a tertiary care hospital accounted for 112 (5.56%) of total 2012 deliveries. Out of these cases, 6.45% were unbooked, depicting the negligence of antenatal care, and 5.8% were found linked to low education levels. [4] The extensive urban-rural gap in the utilization of antenatal care can be determined by the fact that according to reports, 70% of women in the lower quantile of South Asia undergo labor at home in comparison 40% of them deliver without any professional assistance. In Southeast Asia, only 17.7% of lower area women were recorded to use public maternity facilities.[5] A survey from Interior Sindh of Pakistan reported that most rural women have no access to maternity centres within 10km of their living. The authors further stated that the rural residents believed that medical interventions could pose a threat to pregnancy so they preferred untrained midwives over proper maternity centre visits, which could be one of the prime reasons for undiagnosed gestational disorders in these women.[6] Lack of antenatal care utilization could be due to paucity of awareness amongst rural women or the dearth of maternity centres in such underdeveloped areas. Together these factors presented as the key attributes to vascular dementia favouring pre-eclampsia. In rural areas, where barriers to healthcare services and socioeconomic inequality already prevail, this untended rise is a red flag situation. Respective Governments should channel efforts in expanding the accessible maternity setups in these poorly facilitated areas. --Continue